2021
DOI: 10.1177/00207640211001886
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perceived social support and self stigma in caregivers of patients with schizophrenia

Abstract: Background: The study was conducted to determine the relationship between self-stigmatization and perceived social support in caregivers of schizophrenia with patient. Methods: A cross-sectional study design was used. The study sample consisted of 84 participants who cared for schizophrenic patients registered in a community mental health center. In the data collection, the ‘Self-stigmatizing Scale for Families’ and ‘Multidimensional Perceived Social Support Scale’ were used. The data were analyzed via frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Negative stigma from the community indicates that the community is less able to accept the presence of schizophrenic patients in their environment, so it will impact community support for families caring for schizophrenic patients at home [28]. This is as stated by Karaçar and Bademli in their research, namely that when the perceived level of social support decreases in families of schizophrenic patients, this indicates increased stigmatization and vice versa [29]. From the results of this study, it can be stated that families of schizophrenic patients who seek treatment at the outpatient polyclinic at Teuku Umar Hospital, Aceh Jaya Regency, do not make social support an encouragement to carry out care for schizophrenic patients at home.…”
Section: Discussionmentioning
confidence: 91%
“…Negative stigma from the community indicates that the community is less able to accept the presence of schizophrenic patients in their environment, so it will impact community support for families caring for schizophrenic patients at home [28]. This is as stated by Karaçar and Bademli in their research, namely that when the perceived level of social support decreases in families of schizophrenic patients, this indicates increased stigmatization and vice versa [29]. From the results of this study, it can be stated that families of schizophrenic patients who seek treatment at the outpatient polyclinic at Teuku Umar Hospital, Aceh Jaya Regency, do not make social support an encouragement to carry out care for schizophrenic patients at home.…”
Section: Discussionmentioning
confidence: 91%
“…Some previous studies also suggested similar findings, Singh and Kishor (2018) reported that patients with schizophrenia had lower social adjustment compared to patients in the bipolar disorders, but both disorders had lower social support. Kumar et al (2021) reported that poor social adjustment in patients with schizophrenia and bipolar disorder is associated with multiple hospitalizations and significant difference in social adjustment between both groups (Kumar et al, 2018;. found that more bipolar disorder received poor social support from careers, friends and others and frequent relapses are also due to a decrease in social adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with schizophrenia with mild symptoms can live without support; however, other patients with severe symptoms need assistance. A study showed that caregivers who have not received education about schizophrenia experience higher stigma (38). Therefore, education of patients and their caregivers is essential to increase their knowledge about this disease and proper encounter with it.…”
Section: Discussionmentioning
confidence: 99%